Evaluation of CGIAR Program on Water, Land and Ecosystems (WLE) - Batchelor, Charles; Brouder, Sylvie; Coccia, Federica; Fereres, Elias; Rathgebe Eva M.; Soussan, John; Todd, David (CGIAR Independent Evaluation Arrangement, 2016)
The CRP on Water, Land and Ecosystems (WLE) aims to “learn how to intensify farming activities, expand agricultural areas and restore degraded lands, while using natural resources wisely and minimizing harmful impacts on supporting ecosystems.”